The Cambridge companion to popular fiction - Glover, David 1946-; McCracken, Scott (Cambridge companions to topics, 2012)
"Popular commercial fiction emerged in the nineteenth century, with serialised novels and sensational penny dreadfuls. Today it remains a multi-million dollar industry giving pleasure to many, but it is also a field of growing interest for scholars and students of literature. This Companion covers the major developments in the history of popular fiction, with specially commissioned chapters on pulp fiction, bestsellers, and comics and graphic narratives. The volume also examines the public and personal everyday contexts within which popular texts are read, highlighting the ways in which such narratives have circulated across a variety of constantly changing media, including theatre, television, cinema and new computer-based digital forms. Case studies from key genres - crime fiction, romance and Gothic horror - as well as a full chronology and guide to further reading make this collection indispensable to all those interested in this complex and vibrant cultural field"-- Provided by publisher.